The use of M-Learning in Teaching English for Civil Engineering Students - Dharmawati, Dharmawati (Sinkron : Jurnal dan Penelitian Teknik Informatika, 2020)
This research had aimed to describe the use of M-Learning in teaching English for Civil Engineering students at Harapan University of Medan. M-learning as Digital teaching materials were made based on the students need which consist of learning materials. M-learning as Digital teaching materials can be used by lecturer to create more interesting learning materials, by adding videos and animations. The use of M-learning as digital teaching materials was examined based on concepts understanding and students’ response. The subject of this research was 25 students of engineering students. The concepts of understanding were measured by exam test. The students' response was measured based on Likert-scales. The data analysis used was a descriptive statistic. The method of this research was quantitative method. Waterfall model was used in designing M-learning material. The results of this research is the score of students’ conceptual understanding x = (85 ± 8) and students’ response can be categorized very good (percentage of effectiveness are 85%). The results showed that the use of M-learning as digital teaching materials are effective to use in teaching English for civil engineering students at Harapan University of Medan.